Transcriptome and metabolome profiling identify factors potentially involved in pro-vitamin A accumulation in cassava landraces - Olayide, P.; Alexandersson, E.; Tzfadia, O.; Lenman, M.; Gisel, A.; Stavolone, L. (Elsevier, 2023)
Cassava (Manihot esculenta Crantz) is a predominant food security crop in several developing countries. Its storage roots, rich in carbohydrate, are deficient in essential micronutrients, including provitamin A carotenoids.